Trends in economic burden of type 2 diabetes in China: Based on longitudinal claim data - Liu, Xinyi; Zhang, Luying; Chen, Wen (Frontiers in Public Health, 2023)
Objective Diabetes is a major health issue in China that has a significant economic burden on society. Understanding the economic impact of diabetes can help policymakers make informed decisions about healthcare spending and priorities. This study aims to estimate the economic burden of patients with diabetes in an urban setting in China and to identify the impact of hospitalization and complications on health care costs for people with diabetes. Methods The study was conducted in a sample city located in eastern China. All patients diagnosed with diabetes before January 2015 were identified from the official health management information system, and their social demographics and records of their health care uses and costs were extracted from the claim database from 2014 to 2019. Six groups of complications were identified according to ICD-10 codes. The diabetes-related direct medical cost (DM cost) was described for patients in stratified groups. A multiple linear regression model was applied to identify the effect of hospitalization and complications on the DM cost of diabetic patients. Results Our research included 44,994 patients with diabetes, the average annual DM costs for diabetic patients increased from 1,292.72 USD in 2014 to 2,092.87 USD in 2019. The costs of diabetes are closely related to hospitalizations and the type and number of complications. The average annual DM cost of patients who were hospitalized was 2.23 times that of those without hospitalization, and it rose as the number of complications increased. Cardiovascular complications and nephropathic complications were the complications that had the greatest impact on patients’ DM costs, increasing by an average of 65 and 54%, respectively. Conclusion The economic burden of diabetes in urban China has increased significantly. Hospitalization and the type and number of complications have significant impacts on the economic burden of patients with diabetes. Efforts should be made to prevent the development of long-term complications in the population with diabetes.